Analysis of Human Immunodeficiency Virus and Hepatitis B Surface Antigen Examination in Second Trimester Pregnant Women - Dian Hastari Ningrum; Asvia Rahayu (Medistra Medical Journal (MMJ), 2026)
Infections caused by the Hepatitis B virus and Human Immunodeficiency Virus (HIV) remain major global public health concerns, particularly among pregnant women who are at high risk of transmitting infections to their infants through vertical transmission. Transmission may occur during the intrauterine, intrapartum, or postpartum periods. Screening for Hepatitis B surface antigen (HBsAg) and HIV is an essential component of integrated antenatal care aimed at preventing mother-to-child transmission. The purpose of this study was to analyze the relationship between HIV and HBsAg examination results among second trimester pregnant women at Tanjung Haloban Community Health Center. This study employed an analytical observational design with a cross-sectional approach. A total of 25 respondents were selected using a total sampling technique. Data were obtained from laboratory examination results and analyzed using univariate and bivariate analysis with the Chi-Square test at a significance level of 0.05. The results showed that 88% of respondents had non-reactive HIV results and 80% had non-reactive HBsAg results. Bivariate analysis indicated a statistically significant relationship between HIV and HBsAg examination results (p = 0.02 < 0.05). In conclusion, although the majority of pregnant women were not infected, there were still reactive cases that may contribute to vertical transmission, and a significant association between the two infections suggests the possibility of co-infection. Therefore, strengthening routine screening, improving health education, and optimizing prevention programs are necessary.